Integrated project management in the agro-construction complex: efficiency analysis and strategies for improving corporate identity (Economics and region, 2025)
The article explores the importance of integrated project management in the agro-construction complex, emphasizing its crucial role in enhancing the efficiency and success of projects. Integrated project management involves coordinating and combining the key elements of project management—planning, execution, control, and evaluation—into a unified system. In the context of the agro-construction sector, this approach covers the management of construction projects, the production of agricultural machinery, resource distribution, and other related areas. To achieve optimal project outcomes, it is essential to conduct a comprehensive analysis in several areas, including commercial, financial, technical, economic, organizational, social, and environmental analyses. The article highlights that the effectiveness of integrated project management in the agro-construction complex depends on factors such as proper planning, organization, teamwork, technological innovations, risk management, financial control, stakeholder interaction, quality assurance, and continuous staff development. The successful integration of these factors is critically important for enhancing project management efficiency, ensuring the competitiveness of construction enterprises, productive corporate management, and corporate identity. By incorporating these key elements, companies can enhance their ability to manage complex projects effectively, reduce risks, and achieve greater long-term success.
Keywords: agro-construction complex; enterprises; integrated project management; corporate management; corporate identity; efficiency; project analysis